CXCL10 is a novel anti‐angiogenic factor downstream of p53 in cardiomyocytes. Issue 9 (11th May 2022) - Wahyuni, Tri; Tanaka, Shota; Igarashi, Ryuta; Miyake, Yoshiaki; Yamamoto, Ayaha; Mori, Shota; Kametani, Yusuke; Tomimatsu, Masashi; Suzuki, Shota; Yokota, Kosei; Okada, Yoshiaki; Maeda, Makiko; et al.
Abstract: Tumor suppressor protein p53 plays crucial roles in the onset of heart failure. p53 activation results in cardiac dysfunction, at least partially by suppressing angiogenesis. Though p53 has been reported to reduce VEGF production by inhibiting hypoxia‐inducible factor, the anti‐angiogenic property of p53 remains to be fully elucidated in cardiomyocytes. To explore the molecular signals downstream of p53 that regulate vascular function, especially under normoxic conditions, DNA microarray was performed using p53‐overexpressing rat neonatal cardiomyocytes. Among genes induced by more than 2‐fold, we focused on CXCL10, an anti‐angiogenic chemokine. Real‐time PCR revealed that p53 upregulated the CXCL10 expression as well as p21, a well‐known downstream target of p53. Since p53 is known to be activated by doxorubicin (Doxo), we examined the effects of Doxo on the expression of CXCL10 and found that Doxo enhanced the CXCL10 expression, accompanied by p53 induction. Importantly, Doxo‐induced CXCL10 was abrogated by siRNA knockdown of p53, indicating that p53 activation is necessary for Doxo‐induced CXCL10. Next, we examined the effect of hypoxic condition on p53‐mediated induction of CXCL10. Interestingly, CXCL10 was induced by hypoxia and its induction was potentiated by the overexpression of p53. Finally, the conditioned media from cultured cardiomyocytes expressing p53 decreased the tube formation of endothelial cells compared with control, analyzed by angiogenesis assay. However, the inhibition of CXCR3, the receptor of CXCL10, restored the tube formation. These data indicate that CXCL10 is a novel anti‐angiogenic factor downstream of p53 in cardiomyocytes and could contribute to the suppression of vascular function by p53. Abstract : The conditioned media from p53‐expressing cardiomyocytes decreased the tube formation of Rat Aortic Endothelial Cells. The blockade of CXCR3, a receptor of CXCL10, restored the angiogenic activity of the conditioned media from p53‐expressing cardiomyocytes.